ARSIS AND THESIS: A REVIEW OF TWO ELEMENTS OF RHYTHM IN NON-TRADITIONAL MUSIC WRITTEN BY F. H. SMITH VAN WAESBERGHE D.J - -, Sunarto (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2014)
This paper aims to discuss the comparative terms of arsis and thesis in the study of Western music. The purpose of the study is to study the forms of music from the terms of language and its application, because there are many elements of music that are not understandable. Method of this study uses classical literature and musicology approach in which the great phrase rhythm of Gregorian music was more appropriately take a literary term; arsis and thesis. The focus of this study is to discuss the terms of Arsis and Thesis used in the section of rhythm elements of non-traditional music. This study reveals several musical terms in which there are similarities and differences between the rhythm and bars of music. The similarities and differences in the analysis are based on the history of Western music from Gregorian music. Gregorian was monophonic music that still existed in Europe until the 19th century. There were only two phrases in Gregorian music; when Â the melody moved up and when it moved down. In this case, there were two main elements in Gregorian music; they were different in rhythmic and they were in one rhythm of music. Arsis is a hard melody while thesis is a soft melody. It could be said that arsis and thesis are also parts of the dynamics form of music work. Â Keywords: arsis; Thesis; music rhythm; non-traditional music.